Polysilicate aluminum ferric titanium sulfate coagulant and preparation method thereof
By activating coal gangue and preparing polysiliconite iron-aluminum-ferro-titanium coagulant, the threat of residues of existing aluminum salts and iron salt coagulants on human health and water quality in water treatment are solved, and efficient and low-cost wastewater pollutants are achieved.
Patent Information
- Application Number
- CN202411819238.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing aluminum salt and iron salt coagulants have problems with the threat of residues to human health and water quality during the water treatment process, and the cost and efficiency are low, making it difficult to meet the ever-increasing water treatment standards.
Using coal gangue as raw material, polysilicon ferro-aluminum-ferro-titanium coagulant is prepared by calcination activation, acid leaching, titanium doping, pH adjustment, polymerization, centrifugation, and maturation.
It improves the specific surface area and chemical activity of the coagulant, improves the removal rate of wastewater pollutants, reduces the cost of water treatment, and avoids the problem of aluminum and iron residues.
Smart Images

Figure CN119638031A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coagulants, in particular to a polysilicon aluminum sulfate iron titanium coagulant and a preparation method thereof. Background Art
[0002] Coagulation or flocculation is the most commonly used technology for treating pollutants in wastewater. Its purpose is to aggregate fine organic or inorganic particles (such as colloids and suspended particles) in the raw water into large flocs for subsequent removal by sedimentation and filtration processes. In this process, some soluble substances such as natural organic matter (NOM) and metal ions can also be removed together. Coagulants are complex and diverse, including natural coagulants, metal coagulants, mixed coagulants, etc., but due to cost and efficiency reasons, aluminum salts and iron salts are still widely used in my country. However, aluminum salt and iron salt coagulants still have shortcomings. The residual aluminum in the water treated with aluminum salt coagulants will cause harm to the human body, and the water treated with iron salt coagulants will have a higher colorimetric and corrosiveness, which will have a certain impact in the water treatment process. And with the continuous improvement of the sanitary standards of drinking water, seeking low-cost and efficient coagulants is the only way to treat coagulated water.
[0003] In recent years, titanium salts have been increasingly used as raw materials for preparing coagulants, which has attracted widespread attention. The hydrolysis and coagulation process of titanium salt coagulants is different from that of other inorganic salt coagulants. The coagulation process of titanium coagulants is more excellent, with low turbidity at low temperatures, low effluent toxicity, and the concentration level of residual and your number in the coagulated effluent liquid is much lower than that of aluminum / iron coagulants. Therefore, titanium coagulants can solve the shortcomings of traditional aluminum / iron coagulants. In particular, the health risks caused by residual aluminum and the side effects of iron species on subsequent water treatment devices. Summary of the invention
[0004] Technical problems solved by the present invention: The invention is used to provide a polysilicate aluminum sulfate iron titanium coagulant prepared by using coal gangue as raw material, thereby realizing the development and utilization of coal gangue and the low cost and high efficiency of the coagulant.
[0005] The technical solution adopted by the present invention is: First, the present invention provides a method for preparing a polysilicon aluminum sulfate iron titanium coagulant, comprising the following steps: S1 Coal gangue is roasted to obtain modified coal gangue; S2 modified coal gangue is treated by acid leaching to obtain coal gangue acid leaching liquid; S3 The coal gangue acid leaching liquid is subjected to titanium doping, pH adjustment, polymerization, centrifugation and aging to obtain a coagulant.
[0006] According to some preferred embodiments, the gangue after 200 mesh sieve is roasted with anhydrous calcium carbonate and anhydrous sodium carbonate to obtain modified gangue, the mass ratio of anhydrous calcium carbonate and anhydrous sodium carbonate to the gangue is 0.4-1.4:1, and the roasting temperature is 750-1000°C. The modification ratio can be specifically 0.4:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.4:1; the roasting temperature can be specifically 750, 800, 850, 900, 950, 1000°C. The mass ratio of anhydrous calcium carbonate to anhydrous sodium carbonate is 1:1.
[0007] According to some more preferred embodiments, the mass ratio of anhydrous calcium carbonate and anhydrous sodium carbonate to coal gangue is 1:1, and the roasting temperature is 850°C.
[0008] According to some preferred embodiments, the acid leaching treatment: the acid concentration is 2-7 mol / L, the acid leaching time is 1.5-4 h, and the acid leaching temperature is 60-90° C. The acid concentration can be 2, 3, 4, 5, 6, 7 mol / L; the acid leaching time can be 1.5, 2, 2.5, 3, 3.5, 4 h.
[0009] According to some more preferred embodiments, the acid leaching treatment is carried out with an acid concentration of 4 mol / L and a leaching time of 3 h.
[0010] According to some preferred embodiments, titanium doping: titanium tetrachloride is added for doping, the pH value is adjusted to 0.5-3 with sodium hydroxide, and the polymerization reaction is carried out at 40-90°C for 1-6 hours. The polymerization pH can be 0.5, 1, 1.5, 2, 2.5, 3. The polymerization temperature can be 40, 50, 60, 70, 80, 90°C. The polymerization time can be 1, 2, 3, 4, 5, 6 hours.
[0011] According to some preferred embodiments, the pH value is adjusted to 1.5 and the polymerization reaction is carried out at 70°C.
[0012] According to some preferred embodiments, aging: aging at 30-50° C. for 10-15 hours.
[0013] Second, the present invention provides a polysilicate aluminum sulfate iron titanium coagulant obtained by the aforementioned preparation method.
[0014] The beneficial effects achieved by the present invention are: The polysilicon aluminum sulfate iron titanium coagulant provided by the present invention is prepared with coal gangue as raw material, and after activation treatment, the crystalline state inside the coal gangue can be converted into an amorphous state, and it has a large specific surface area and high chemical activity. After activation modification, it is then subjected to acid leaching, polymerization, centrifugation, aging and drying treatment to prepare a polysilicon aluminum titanium iron coagulant. By optimizing the roasting temperature, modification ratio, acid concentration, polymerization pH, polymerization temperature and polymerization time, the coagulation performance of the coagulant can be improved, thereby improving the wastewater pollutant removal rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is the result graph of the effect of roasting temperature on the leaching rate of iron, aluminum and silicon; Figure 2 This is the result diagram of the modification comparison of iron, aluminum and silicon leaching rates; Figure 3 This is the result graph of the effect of acid concentration on the leaching rate of iron, aluminum and silicon; Figure 4 This is the result graph of the effect of acid leaching time on the leaching rate of iron, aluminum and silicon; Figure 5 The effect of calcination temperature on turbidity (a), UV 254 (b) COD Cr (c) Result graph of removal rate; Figure 6 For modified comparison of turbidity (a), UV 254 (b) COD Cr (c) Result graph of removal rate; Figure 7 The effect of acid concentration on turbidity (a) and UV 254 (b) COD Cr (c) Result graph of removal rate; Figure 8 The effect of acid leaching time on turbidity (a) and UV 254 (b) COD Cr (c) Result graph of removal rate; Fig. 9 The effect of polymerization pH on turbidity (a) and UV 254 (b) COD Cr (c) Result graph of removal rate; Fig.10 is the effect of polymerization temperature on turbidity (a), UV 254 (b) COD Cr (c) Result graph of removal rate; Fig.11 is the effect of polymerization time on turbidity (a), UV 254 (b) COD Cr (c) Result graph of removal rate; Fig.12It is a flow chart of the detection method of Fe2O3; Fig.13 It is a flow chart of the detection method of Al2O3; Fig.14 It is a flow chart of the detection method of SiO2; Fig.15 This is the flow chart for the determination of CODcr. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0017] In the present invention, the coal gangue used is taken from the gangue mountain in Panzhihua City, Sichuan Province. The main mineral phases of the coal gangue are quartz, calcite, kaolin and kaolinite mixed layer. The main chemical components are shown in Table 1.
[0018] Table 1 Chemical composition of coal gangue raw materials
[0019] The invention uses coal gangue as raw material and prepares polysilicon aluminum sulfate iron titanium through thermal activation, acid leaching, polymerization, centrifugation and aging.
[0020] Step 1: Calcination and activation of coal gangue Since the activity of coal gangue itself is low, the ion precipitation rate is not high during direct acid leaching treatment, so the coal gangue is activated before acid leaching. The coal gangue after passing through a 200-mesh sieve is mixed evenly with anhydrous calcium carbonate and anhydrous sodium carbonate (mass ratio 1:1), put into a crucible and then placed in a muffle furnace for roasting. Roast at a certain heating rate to a predetermined temperature for 2 hours, take out the roasted coal gangue and cool it naturally to obtain the activated modified coal gangue powder.
[0021] Step 2: Acid leaching of coal gangue Sulfuric acid is used for acid leaching because hydrochloric acid is volatile and has a poor acid leaching effect. Coal gangue contains clay minerals (Al2O3·2SiO2·2H2O). A certain concentration of acid at high temperature can increase the leaching rate of Al2O3, and the following reactions will occur: Al2O3·2SiO2·2H2O +3H2SO4→Al2(SO4)3+2H2SiO3+3H2O The main reactions with Fe2O3 in sulfuric acid leaching of coal gangue are: Fe2O3+H2SO4→Fe2(SO4)3+H2O First, weigh 20g of activated and modified coal gangue powder and put it into a 300ml conical flask with weighing paper, add a certain proportion of sulfuric acid solution, put a magnetic rotor in a beaker, seal the beaker mouth with plastic wrap, and place it in a constant temperature water bath and stir it at a certain temperature for a period of time. After taking it out, pour it into a centrifuge tube and centrifuge it in a centrifuge at 4000 r / min for 5 minutes to separate the solid and liquid. The liquid in the centrifuge tube is the acid leaching solution. Complexometric titration of the acid leaching solution can obtain the content of metal ions in the acid leaching solution and the leaching rate.
[0022] Step 3: Preparation of polysilicon aluminum sulfate iron titanium The acid leaching solution obtained after acid leaching of the modified coal gangue and the titanium tetrachloride solution are mixed evenly in a 100ml beaker according to a certain iron-titanium ratio, and the pH of the mixed solution is adjusted to a preset value of 1.5 using 400g / L NaOH. After adding the magnetic rotor, seal it with plastic wrap and place it in a magnetic stirring pot to polymerize at a preset temperature for a period of time. After the end, take out the sample solution in the beaker and pour it into a centrifuge tube, centrifuge it at 4000 r / min for 5 min, take the supernatant and place it in a 100ml beaker, and mature it at a constant temperature for a period of time. After the end, take out the sample and put it in an oven to dry at 105°C. After drying, grind the sample to obtain the finished product of polysilicon aluminum sulfate iron titanium (PSAFT).
[0023] The polyaluminum ferro-titanium silicate sulfate prepared above was subjected to a coagulation experiment.
[0024] Preparation of experimental simulated wastewater: Take out the experimental kaolin stock solution and add ultrapure water to dilute it to 1L, so that the turbidity of the solution reaches 100±5NTU to obtain simulated wastewater; then weigh 0.2125g of dry potassium hydrogen phthalate and add it to the prepared simulated wastewater, shake it thoroughly and set aside. The COD of the simulated wastewater Cr Theoretical value: 500mg Finally, the UV of the simulated wastewater can be measured by a laboratory spectrophotometer. 254 The absorbance is 2.168±0.002Abs.
[0025] Coagulation experiment: Use a pipette to take 300ml of simulated wastewater into a 500ml beaker, add an appropriate amount of PSAFT, adjust the pH to 8 with 0.5mol / L sulfuric acid solution or sodium hydroxide solution, use a JJ-4 six-joint mixer to stir quickly for 60s and slowly for 600s, then remove the stirring paddle. After standing for 1800s, take the upper clear liquid of the wastewater for the determination of water quality indicators.
[0026] Metal detection method in coal gangue acid leaching solution: The detection method of metal ions in coal gangue acid leaching solution shall refer to the method of GB / T14563-2020.
[0027] (1) The detection process of Fe2O3 is as follows Fig.12 shown.
[0028] The calculation formula of Fe2O3 content is as follows:
[0029] (2) The detection process of Al2O3 is as follows Fig.13 shown.
[0030] Al2O3 content calculation formula:
[0031] (3) The detection process of SiO2 is as follows Fig.14 shown.
[0032] The SiO2 content is calculated as follows:
[0033] Determination of water quality indicators: (1) Turbidity determination Take an appropriate amount of water sample and put it into a turbidity vial. Use a digital turbidity meter to measure it. Wait until the data on the turbidity meter stops jumping before reading. The data in the range is the turbidity.
[0034] (2) UV 254 Determination of The absorbance of the supernatant was measured at 254 nm on an ultraviolet spectrophotometer, which is UV 254 .
[0035] (3) The CODcr determination process is as follows: Fig.15 shown.
[0036] CODcr content calculation formula:
[0037] Experiment 1: Effect of different roasting temperatures on metal ion leaching rate Take 20g of activated coal gangue, and carry out acid leaching experiment under the conditions of acid concentration of 6mol / L, acid leaching time of 2.5h and acid leaching temperature of 75℃, change the roasting temperature (750℃, 800℃, 850℃, 900℃, 950℃, 1000℃), and determine the content of iron ion, aluminum ion and silicon ion in the acid leaching solution. The experimental results are as follows: Figure 1 shown.
[0038] Depend on Figure 1The results show that the leaching rates of ferric oxide and aluminum oxide increase with the increase of roasting temperature. At 850℃, the leaching rate and the sum of metal ions reach the highest, the leaching rate of ferric oxide reaches 35.69%, the leaching rate of aluminum oxide reaches 35.27%, and the leaching rate of silicon dioxide increases with the increase of roasting temperature. Since the roasting temperature in this experiment is 1000℃, the leaching rate of silicon dioxide is the highest at 1000℃. The sum of metal ions reaches 7.589g / mL at 850℃. This may be because the coal gangue becomes loose after roasting. Under high-temperature roasting, the crystal state inside the coal gangue will change from crystalline to amorphous. Kaolinite has a large specific surface area and high chemical reaction activity, which can make aluminum oxide leached by acid. However, when the temperature continues to rise, mullite and cristobalite will be formed, resulting in a decrease in the activity of coal gangue and a decrease in the leaching rate of metal ions. In summary, the calcination temperature is 800°C, at which time the iron ions are 1.82%, the aluminum ions are 5.47%, and the silicon ions are 0.299%.
[0039] Experiment 2: Effect of modification ratio on metal ion leaching Take 20g of activated coal gangue, and carry out acid leaching experiment under the conditions of roasting temperature of 850℃, acid concentration of 6mol / L, acid leaching time of 2.5h and acid leaching temperature of 75℃, change the modification ratio of calcium carbonate and sodium carbonate (0.4:1, 0.6:1, 0.8:1, 1:1, 1.2:1 and 1.4:1) to determine the content of metal ions in the acid leaching solution. The experimental results are as follows: Figure 2 shown.
[0040] Depend on Figure 2 The results show that the leaching rates of ferric oxide, aluminum oxide and silicon dioxide increase with the increase of the modification ratio of calcium carbonate and sodium carbonate. At 1:1, the leaching rate and the total amount of metal ions reach the highest, with the leaching rate of ferric oxide reaching 59.42%, the leaching rate of aluminum oxide reaching 54.5%, and the leaching rate of silicon dioxide reaching 0.0133%. The total amount of metal ions reaches 11.851 g / mL. This may be caused by the fact that when the content of calcium carbonate and sodium carbonate is low, calcium carbonate and sodium carbonate cannot be fully mixed with coal gangue to react, and less CO2 is generated, which makes the specific surface area of coal gangue smaller. Coal gangue is difficult to dissolve in acid, resulting in that iron and aluminum ions cannot be fully extracted by acid leaching. The presence of calcium carbonate and sodium carbonate can make the acid leaching reaction of coal gangue proceed in a positive direction. After 0.6:1, the ion leaching rate rises rapidly, and at 1:1, the coal gangue reaction reaches equilibrium, and the ion leaching rate reaches a peak. After 1:1, due to the excessive calcium carbonate and sodium carbonate, part of them cannot be mixed with coal gangue to react, and the ion leaching rate tends to balance. In summary, the metal ion leaching rate is best when the modification ratio is 1:1, at which time the iron ion is 3.02%, the aluminum ion is 8.45%, and the silicon ion is 0.381%.
[0041] Experiment 3: Effect of acid concentration on metal ion leaching rate Take 20g activated coal gangue, and carry out acid leaching experiment under the conditions of roasting temperature of 850℃, modification ratio of 1:1, acid leaching time of 2.5h and acid leaching temperature of 85℃, change the acid concentration (2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L) to determine the content of metal ions in the acid leaching solution. The experimental results are as follows: Figure 3 shown.
[0042] Depend on Figure 3 The results show that the leaching rates of ferric oxide, aluminum oxide and silicon dioxide increase with the increase of sulfuric acid concentration. At 4 mol / L, the leaching rate and the total amount of metal ions reach the highest, with the leaching rate of ferric oxide reaching 38.65%, the leaching rate of aluminum oxide reaching 53.57%, and the leaching rate of silicon dioxide reaching 0.02%. The total amount of ions reaches 10.806 g / mL. After the acid concentration exceeds 4 mol / L, the leaching rate of metal ions decreases with the increase of time, and the total amount of metal ions increases slowly. This may be because sulfate can improve the electrical neutrality and adsorption bridging ability of copolymers such as iron and aluminum ions, and enhance the coagulation ability of aluminum and iron. It can increase the degree of polymerization of copolymers such as iron and aluminum ions, increase the charge number, and it is easier to combine with negatively charged particles to form flocs during the coagulation process. The flocculation process continues to combine, grow, and finally settle. The removal rate reaches the highest at 4 mol / L. When the amount of sulfate introduced is too large, its stability will change, and precipitation will easily occur, resulting in a decrease in the leaching rate of metal ions. In summary, the ion leaching rate is best when the acid concentration is 4 mol / L, at which time the iron ion is 1.97%, the aluminum ion is 8.3%, and the silicon ion is 0.536%.
[0043] Experiment 4: Effect of acid leaching time on metal ion leaching rate Take 20g activated coal gangue, and carry out acid leaching experiment under the conditions of roasting temperature of 850℃, modification ratio of 1:1, acid leaching temperature of 85℃, acid concentration of 4mol / L, change the acid leaching time (1.5h, 2h, 2.5h, 3h, 3.5h, 4h), and determine the content of metal ions in the acid leaching solution. The experimental results are as follows: Figure 4 shown.
[0044] Depend on Figure 4The results show that the leaching rates of ferric oxide, aluminum oxide and silicon dioxide increase with the increase of acid leaching time. At 3 hours, the leaching rate and the total amount of metal ions reach the highest, with the leaching rate of ferric oxide reaching 40.58%, the leaching rate of aluminum oxide reaching 43%, and the leaching rate of silicon dioxide reaching 0.021%, while the total amount of metal ions reaches 9.257g / mL. As the acid concentration continues to increase, the leaching rates of iron, aluminum and silicon ions begin to decrease, and the total amount of metal ions increases and decreases slowly. This may be because when the acid leaching time is less than 3 hours, iron and aluminum ions will react with sulfate (SO4 2- ) react to form insoluble salts, which enter the filter residue and are separated out after centrifugation. This results in a low leaching rate for iron and aluminum ions. After 3 hours, iron and aluminum ions may also react with residual sulfate ions to form corresponding complex complexes, which will remain in the acid leaching solution obtained after centrifugation. Since this experiment is carried out by complexometric titration with EDTA, the stability of these complex complexes with iron and aluminum ions is much higher than the stability of the complexes formed by EDTA with iron and aluminum ions. During titration, EDTA cannot titrate and measure the part of iron and aluminum ions that form complex complexes, resulting in a decrease in the leaching rate of metal ions. In summary, the ion leaching rate is best when the acid leaching time is 3 hours, at which time the iron ion is 2.06%, the aluminum ion is 6.67%, and the silicon ion is 0.527%.
[0045] Test 5: Effect of calcination temperature on PSAFT coagulation effect Take 20g of activated coal gangue, and carry out acid leaching experiment under the conditions of acid concentration of 6mol / L, acid leaching time of 2.5h, and acid leaching temperature of 75℃, change the roasting temperature (750℃, 800℃, 850℃, 900℃, 950℃, 1000℃), take 20ml of acid leaching solution, add titanium tetrachloride according to a certain iron-titanium ratio, adjust the pH to 1.5 with 400g / L sodium hydroxide, and polymerize at 70℃. After the polymerization reaction, take out the beaker and place it in a 40℃ water bath for aging for 12h, and then carry out coagulation experiment and analysis of PSAFT after polymerization at different polymerization temperatures. The results are as follows Figure 5 shown.
[0046] Depend on Figure 5It can be seen that the removal rate of pollutant indicators in wastewater increases with the increase of the roasting temperature of coal gangue. When the roasting temperature reaches 850℃, the removal rate of wastewater pollutants reaches the highest. This may be because the coal gangue will become loose after roasting. Under high-temperature roasting, the crystal state inside the coal gangue will change from crystalline to amorphous. Kaolinite has a large specific surface area and high chemical reaction activity, which can cause aluminum oxide to be leached out by acid. However, when the temperature continues to rise, mullite and cristobalite will be formed, resulting in a decrease in the activity of coal gangue and a decrease in the leaching rate of metal ions. In summary, when the roasting temperature reaches 850℃, the removal rate of pollutants in wastewater is optimal. At this time, COD Cr 、UV 254 The removal rates of water, turbidity and humidity were 40.93%, 34.29% and 95.9% respectively.
[0047] Test 6: Effect of modification ratio on PSAFT coagulation effect Take 20g of activated coal gangue, and carry out acid leaching experiment under the conditions of roasting temperature of 850℃, acid concentration of 6mol / L, acid leaching time of 2.5h and acid leaching temperature of 75℃, change the modification ratio (0.4:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.4:1), take 20ml of acid leaching solution and add titanium tetrachloride according to a certain iron-titanium ratio, adjust the pH to 1.5 with 400g / L sodium hydroxide, and polymerize at 70℃. After the polymerization reaction, take out the beaker and place it in a 40℃ water bath for aging for 12h, and then carry out coagulation experiment and analysis of PSAFT after polymerization at different polymerization temperatures. The results are as follows Figure 6 shown.
[0048] Depend on Figure 6 The results show that the removal rate of pollutant indicators in wastewater increases with the increase of the modification ratio of coal gangue. When the modification ratio is 1:1, the removal rate of wastewater pollutants is the highest. The leaching rate of Si is very low, while the iron and aluminum ions continue to increase with the increase of the modification ratio. When the content of calcium carbonate and sodium carbonate is low, calcium carbonate and sodium carbonate cannot be fully mixed and reacted with coal gangue, and less CO2 is generated, which makes the specific surface area of coal gangue smaller. Coal gangue is difficult to dissolve in acid, resulting in iron and aluminum ions cannot be fully extracted by acid leaching. The presence of calcium carbonate and sodium carbonate can make the acid leaching reaction of coal gangue proceed in the positive direction. After 0.6:1, the ion leaching rate increases rapidly, and at 1:1, the reaction of coal gangue reaches equilibrium, and the ion leaching rate reaches its peak. After 1:1, due to the excessive calcium carbonate and sodium carbonate cannot be mixed and reacted with coal gangue, the ion leaching rate tends to equilibrium. In summary, when the modification ratio reaches 1:1, the removal rate of pollutants in wastewater is the best. At this time, COD Cr 、UV 254 The removal rates of water, turbidity and humidity were 36.83%, 37.81% and 96.6% respectively.
[0049] Experiment 7: Effect of acid concentration on PSAFT coagulation effect Take 20g activated coal gangue, and carry out acid leaching experiment under the conditions of roasting temperature of 850℃, modification ratio of 1:1, acid concentration of 6mol / L, acid leaching time of 2.5h and acid leaching temperature of 75℃, change the acid concentration (2 mol / L, 3mol / L, 4mol / L, 5mol / L, 6mol / L, 7mol / L), take 20ml acid leaching solution and add titanium tetrachloride according to a certain iron-titanium ratio, adjust the pH to 1.5 with 400g / L sodium hydroxide, and polymerize at 70℃. After the polymerization reaction, take out the beaker and place it in a 40℃ water bath for aging for 12h, and then carry out coagulation experiment and analysis of PSAFT after polymerization at different polymerization temperatures. The results are as follows Figure 7 shown.
[0050] Depend on Figure 7 The results show that the removal rate of pollutant indicators in wastewater increases with the increase of acid concentration, and the removal rate reaches the highest when the acid concentration reaches 4 mol / L. This may be because sulfate can improve the electrical neutrality and adsorption bridging ability of copolymers such as iron and aluminum ions, and enhance the aluminum-iron coagulation ability. It can increase the degree of polymerization of copolymers such as iron and aluminum ions, increase the charge number, and make it easier to combine with negatively charged particles to form flocs during the coagulation process. The flocculation process continues to combine, grow, and finally settle. The removal rate is the highest at 4 mol / L. When the amount of sulfate introduced is too large, its stability will change, and precipitation is easy to occur, resulting in a decrease in the removal rate of wastewater pollution indicators. In summary, when the acid concentration reaches 4 mol / L, the pollutant removal rate in wastewater is optimal. The COD at this time Cr 、UV 254 The removal rates of water, turbidity and humidity were 57.33%, 38.5% and 95.69% respectively.
[0051] Test 8: Effect of acid leaching time on PSAFT coagulation effect Take 20g of activated coal gangue, and carry out acid leaching experiment under the conditions of roasting temperature of 850℃, modification ratio of 1:1, acid concentration of 6mol / L, acid leaching temperature of 70℃, and acid concentration of 4 mol / L, change the acid leaching time (1.5h, 2h, 2.5h, 3h, 3.5h, 4h), take 20ml of acid leaching solution and add titanium tetrachloride according to a certain iron-titanium ratio, adjust the pH to 1.5 with 400g / L sodium hydroxide, and polymerize at 70℃. After the polymerization reaction, take out the beaker and place it in a 40℃ water bath for aging for 12h. Then, the PSAFT after polymerization at different polymerization temperatures is subjected to coagulation experiment and analysis. The results are as follows: Figure 8 shown.
[0052] Depend on Figure 8The results show that the removal rate of pollutant indicators in wastewater increases with the increase of acid leaching time, and the removal rate reaches the highest when the acid leaching time is 3 hours. This may be because when the acid leaching time is less than 3 hours, iron ions and aluminum ions will react with sulfate ions (SO4 2- ) react to form insoluble salts, which enter the filter residue and are separated out after centrifugation. This results in a low leaching rate for iron and aluminum ions. After 3 hours, iron and aluminum ions may also react with residual sulfate ions to form corresponding complex complexes, which will remain in the acid leaching solution obtained after centrifugation. Since this experiment is carried out by EDTA complexation titration, these complex complexes are more stable than the complexes formed by EDTA and ions, so they cannot be titrated accurately during titration. This results in a lower removal rate of wastewater pollutants. In summary, when the acid leaching time is 3 hours, the removal rate of pollutants in wastewater is optimal. The COD at this time is Cr 、UV 254 The removal rates of water, turbidity and humidity were 77.6%, 36.21% and 96.03% respectively.
[0053] Experiment 9: Effect of polymerization pH on PSAFT coagulation effect Take 20ml of coal gangue acid leaching solution and add titanium tetrachloride according to a certain iron-titanium ratio, adjust the pH with sodium hydroxide (0.5, 1, 1.5, 2, 2.5, 3), and react at a polymerization temperature of 70℃ for 2.5h. After the polymerization reaction is completed, take out the beaker and place it in a 40℃ water bath for 12h. Then, the PSAFT after polymerization at different polymerization temperatures is subjected to coagulation experiment analysis. The results are as follows Fig. 9 shown.
[0054] Depend on Fig. 9 The results show that the removal rate of pollutant indicators in wastewater increases with the increase of polymerization pH, and the removal rate reaches the highest when the polymerization pH is 1.5. This may be because with the increase of pH, Ala and Fea, which determine the performance of the coagulant, will slowly transform into Alb, Feb or Alc, Fec. The electrical neutralization, adsorption bridging and net sweeping effects of the coagulation sample will be strengthened to a certain extent. In this case, the colloid in the wastewater will deviate from the steady-state equilibrium, and the removal rate of pollutants in the wastewater will also increase. When the pH continues to rise, the Alc produced in the coagulant is positively correlated with the increase or decrease in the alkalinity of the polymerization solution. Therefore, the hydrolysis of Al and Fe will proceed in the direction of Alc generation. This leads to the formation of sodium hydroxide sol precipitation, and the curling of the molecular chain leads to the weakening of the bridging effect, which makes the coagulant performance worse, resulting in a decrease in the removal rate of wastewater pollutants. In summary, when the polymerization pH is 1.5, the removal rate of pollutants in wastewater is the best. At this time, the COD Cr 、UV 254 , and turbidity removal rates were 62.4%, 37.2%, and 96.84%, respectively.
[0055] Test 10: Effect of polymerization temperature on PSAFT coagulation effect Take 20ml of coal gangue acid leaching solution, add titanium tetrachloride according to a certain iron-titanium ratio, adjust the pH to 1.5 with 400g / L sodium hydroxide, change the polymerization temperature (40℃, 50℃, 60℃, 70℃, 80℃, 90℃) for 2.5h, and after the polymerization reaction, take out the beaker and place it in a 40℃ water bath for aging for 12h. Then, conduct coagulation experiment analysis on PSAFT after polymerization at different polymerization temperatures. The results are as follows Fig.10 shown.
[0056] Depend on Fig.10 The results show that the removal rate of pollutant indicators in wastewater increases with the increase of polymerization temperature, and the removal rate reaches the highest when the polymerization temperature is 70°C. This may be because in the process from 40°C to 70°C, as the polymerization temperature increases, the rate of polymerization reaction will be accelerated, the hydroxyl content on the copolymer will increase, the molecular chain of the copolymer will become longer, the adsorption bridging and net capture and sweeping effects will be strengthened, the polymerization degree of the coagulant will increase, and the coagulation performance will increase. After the polymerization temperature reaches 70°C, the polymerization reaction reaches equilibrium, but the alkalinity increases, and the metal ions will transform towards Alc and Fec. This type of polymer is not stable enough, which reduces the polymerization degree of the coagulant sample and reduces the wastewater removal rate. In summary, the pollutant removal rate is best when the polymerization temperature is 70°C. The wastewater pollutant COD Cr 、UV 254 , and turbidity removal rates were 47.2%, 36.8%, and 94.68%, respectively.
[0057] Experiment 11: Effect of polymerization time on PSAFT coagulation effect Take 20ml of coal gangue acid leaching solution, add titanium tetrachloride according to a certain iron-titanium ratio, adjust the pH to 1.5 with 400g / L sodium hydroxide, set the polymerization temperature to 70℃, and change the polymerization time (1h, 2h, 3h, 4h, 5h, 6h) for polymerization reaction. After the reaction, take out the beaker and place it in a 40℃ water bath for aging for 12h. Then, conduct coagulation experiment analysis on PSAFT after polymerization at different polymerization pH. The results are as follows Fig.11 shown.
[0058] Depend on Fig.11 The results show that the removal rate of pollutant indicators in wastewater increases with the increase of polymerization time, and the removal rate reaches the highest when the polymerization temperature is 3h. This may be because from 1h to 3h, as the polymerization time increases, the length of the polymer chain of the coagulant increases, forming a hydroxyl copolymer, which enhances the adsorption bridging effect in the coagulation process, gradually improves the coagulation effect, and increases the pollutant removal rate. After reaching the optimum temperature of 3h, the OH in the polymerization solution increases. -The content gradually decreases, the content of the generated hydroxyl complex decreases, the polymerization reaction of the coagulant proceeds in the reverse direction, the degree of polymerization of the coagulant decreases, and the removal rate of pollutants decreases. In summary, the best pollutant removal is achieved when the polymerization time is 3h. Cr 、UV 254 , and turbidity removal rates were 52%, 36.7%, and 93.68%, respectively.
Claims
1. A method for preparing a polysilicon aluminum sulfate iron titanium coagulant, characterized in that: The steps include: S1 coal gangue is roasted to obtain modified coal gangue; The S2 modified coal gangue is treated by acid leaching to obtain coal gangue acid leaching liquid; The S3 coal gangue acid leaching liquid is subjected to titanium doping, pH adjustment, polymerization, centrifugation and aging to obtain a coagulant.
2. The preparation method of polysilicon aluminum sulfate iron titanium coagulant according to claim 1, characterized in that: The coal gangue after being sieved through 200 meshes is roasted with anhydrous calcium carbonate and anhydrous sodium carbonate to obtain modified coal gangue, the mass ratio of anhydrous calcium carbonate and anhydrous sodium carbonate to the coal gangue is 0.4-1.4:1, and the roasting temperature is 750-1000°C; the mass ratio of anhydrous calcium carbonate to anhydrous sodium carbonate is 1:
1.
3. The preparation method of polysilicon aluminum sulfate iron titanium coagulant according to claim 2, characterized in that, The mass ratio of anhydrous calcium carbonate and anhydrous sodium carbonate to coal gangue is 1:1, and the roasting temperature is 850°C.
4. The preparation method of polysilicon aluminum sulfate iron titanium coagulant according to claim 1, characterized in that: Acid leaching treatment: acid concentration is 2-7 mol / L, acid leaching time is 1.5-4h, and acid leaching temperature is 60-90℃.
5. The preparation method of polysilicon aluminum sulfate iron titanium coagulant according to claim 4, characterized in that, Acid leaching treatment: the acid concentration is 4 mol / L and the acid leaching time is 3 h.
6. The preparation method of polysilicon aluminum sulfate iron titanium coagulant according to claim 1, characterized in that: Titanium doping: Add titanium tetrachloride for doping, adjust the pH value to 0.5-3 with sodium hydroxide, and carry out polymerization reaction at 40-90°C for 1-6 hours.
7. The method for preparing the aluminum ferro-titanium silicate sulfate coagulant according to claim 6, characterized in that: The pH value was adjusted to 1.5, and the polymerization reaction was carried out at 70°C.
8. The method for preparing the polysilicon aluminum sulfate iron titanium coagulant according to claim 1, characterized in that: Ripening: Ripen at 30-50℃ for 10-15h.
9. A polysilicate aluminum sulfate iron titanium coagulant obtained by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method for separation of aluminum and iron from acid leaching solution of coal gangue with high iron content
CN102515280A
Method for preparing high performance polysilicate ferric aluminum sulfate from coal gangue
CN107021552A
Method for preparing polyaluminum ferric titanium sulfate
CN115092967A
Method for preparing polysilicate aluminum ferric flocculant from coal gangue
CN116022801A
METHOD FOR PRODUCING AN ALUMINUM-SILICON COAGULANT-FLOCCULANT
RU2009139266A